OPTIMIZING AIR PRESSURE TO IMPROVE THE EFFICIENCY OF BOTTLE AND CAN WASTE PRESSING ON PNEUMATIC MACHINES - Maharani, Arinda Dinda (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
Abstract. The issue of plastic bottle and can waste continues to grow alongside increasing consumption, necessitating efficient waste management solutions. This study aims to optimize air pressure in a pneumatic-based waste compactor to improve the efficiency of compressing bottles and cans. An experimental method was employed, varying air pressure (6, 7, and 8 bar) and pressing time (10, 20, and 30 seconds). The results show that a combination of 8 bar pressure and 30 seconds pressing time yields optimal compaction, reducing can volume by up to 70,75% and plastic bottle volume by up to 62,87% of their initial sizes. The PLC and sensor-based automation system significantly enhances process efficiency and reliability. These findings highlight the importance of proper air pressure adjustment for energy efficiency, effective compaction, and tool longevity, making this pneumatic machine highly promising for sustainable inorganic waste management.